2016
DOI: 10.1016/j.biombioe.2016.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Storage of whole-tree chips from high-density energy plantations of Eucalyptus in Brazil

Abstract: In this paper, the drying of whole-tree chip (WTC) storage from young Eucalyptus plantation managed at short-rotation coppice in Brazil was studies. The biomass was converted from high-density energy plantations of Eucalyptus grandis at 2 years old into four piles. Wood chip particles had 5, 15, and 30 mm length were disposed on a paved surface to evaluate the effect on the chip drying. An additional covered pile (30-mm wood chip) was installed to evaluate the effect of coverage condition. The non-ventilated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Alguns estudos já comprovaram a melhor qualidade de grãos de café como exemplo, plantados em sistemas agroflorestais em consórcio com Eucalyptus spp., que favorecidos pela sombra, resultarão em uma produtividade mais contínua e sustentável (Ehrenbergerová et al 2016;Petit-Aldana et al 2017). Para plantios mais adensados há uma maior quantidade de biomassa por área, o que pode favorecer uma rotação mais curta de plantio, assim como um retorno financeiro a curto prazo (Eufrade Junior et al 2016).…”
Section: Excentricidade Da Medulaunclassified
“…Alguns estudos já comprovaram a melhor qualidade de grãos de café como exemplo, plantados em sistemas agroflorestais em consórcio com Eucalyptus spp., que favorecidos pela sombra, resultarão em uma produtividade mais contínua e sustentável (Ehrenbergerová et al 2016;Petit-Aldana et al 2017). Para plantios mais adensados há uma maior quantidade de biomassa por área, o que pode favorecer uma rotação mais curta de plantio, assim como um retorno financeiro a curto prazo (Eufrade Junior et al 2016).…”
Section: Excentricidade Da Medulaunclassified
“…The drying of wood is characterized by two outflows of water (capillary and diffusion movement), which occur simultaneously during the process. As discussed in the literature [48,49], initially, moisture is reduced predominantly by capillary movement (free or capillary water) up to the fiber saturation point (FSP) and, subsequently, hygroscopic or impregnation water (adsorbed to the cell walls) is released by diffusion movement. Thus, the moisture loss in chip piles is lower than in logs in tropical conditions, since there is a lack of ventilation inside the piles to maintain capillary movement for longer, which also favors a greater MC gradient from the interior to the edge of the pile.…”
Section: Wood Moisture Content During Storagementioning
confidence: 99%
“…The results show that supplying the thermoelectric plant is more expensive in Supply Chain I, which is explained by the higher demand for biomass due to its high MC regardless of the storage time in the field. Some studies have suggested that one way to reduce this cost is to store and protect the wood chips using some form of cover [48].…”
Section: Forest Operational Costsmentioning
confidence: 99%
“…Chipping increases the bulk density and facilitates transportation [102,104,[113][114][115]. For example, Pecenka et al [116] described the potential for deploying and adapting harvesting systems in Brazil for SRWCs, where there is existing experience in the development of equipment [97] and different drying methods in chip production [117].…”
Section: Energies 2019 12 X For Peer Review 9 Of 22mentioning
confidence: 99%